2014
DOI: 10.1007/s10773-014-2022-z
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Split Octonions and Their Transformation in SO(7) Symmetry

Abstract: Generators of SO(8) group have been described by using direct product of the Gamma matrices and the Pauli Sigma matrices. We have obtained these generators in terms of generalized split octonion also. These generators have been used to describe the rotational transformation of vectors for SO(7) symmetry group.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This ubiquitous appearance of three entities at a vertex in physics has been suggestive of connections to other areas of mathematics. Thus, quaternionic and octonionic symmetries for braids on three strands, their group structure, and triplets of half-odd integer labels have been discussed for the standard model of particle physics [105] and quantum gravity [106], as also the closely related study of knots [107]; see also [108]. A book on division algebras in particle physics is additionally helpful [109].…”
Section: Geometric Viewmentioning
confidence: 99%
“…This ubiquitous appearance of three entities at a vertex in physics has been suggestive of connections to other areas of mathematics. Thus, quaternionic and octonionic symmetries for braids on three strands, their group structure, and triplets of half-odd integer labels have been discussed for the standard model of particle physics [105] and quantum gravity [106], as also the closely related study of knots [107]; see also [108]. A book on division algebras in particle physics is additionally helpful [109].…”
Section: Geometric Viewmentioning
confidence: 99%
“…In physical applications, split octonions were used to provide possible explanation for the existence of three generations of fermionic elementary particles [41] [42]. In [43] generators of ( )…”
Section: Introductionmentioning
confidence: 99%
“…Split octonions were used to provide possible explanation for the existence of three generations of fermionic elementary particles [40,41]. In [42] generators of SO (8) and SO(7) groups were obtained and have been used to describe the rotational transformation in 7-dimensional space. In [43][44][45] real reducible 16 × 16-matrix representation of SO(4, 4) group utilizing the Clifford algebra approach was constructed and it was shown that there are two inequivalent real 8 × 8 irreducible basic spinor representations, potential physical applications for 8-dimensional electrodynamics [44] and gravity [45] was also considered.…”
Section: Introductionmentioning
confidence: 99%